(untitled) (المجلة الدولية للعلوم المالية والإدارية والاقتصادية, 2026)
Foreign trade has an influential role in economic growth, and this is represented in both exports, which is the process that Through it, surplus goods are exported to various countries, and capital and intermediate goods are imported Consumer and primary goods, as capital, intermediate and primary goods are used to achieve an increase in domestic product As for durable and non-durable consumer goods, they are used to meet the growing domestic demand For most countries of the world. This study aims to analyze indicators foreign trade in Iraq and Saudi Arabia, for the period 2003-2022. To reach the objectives of the study and prove its hypothesis, the descriptive analysis method was adopted for the data which related to Iraq and Saudi Arabia, as well as the analysis econometrics model impact of foreign trade on the economic growth comparative study the study concluding: in Iraq The results showed that merchandise exports have a direct and significant impact on output, Long-term relationship: It showed that the relationship between merchandise exports and imports and the total labor force It has a positive and significant relationship with the gross domestic product, while the inflation rate has an inverse and significant relationship Significant. In the Saudi Arabia The results showed that merchandise exports have a direct impact on the GDP, but they are not significant Significance level, The long-term relationship: It was found that the relationship between commodity exports and imports, the inflation rate, and output The gross domestic product is related to a positive but insignificant relationship, while the global forces are related to a positive relationship. And significant with GDP.